Development of a flow chamber system for the reproducible in vitro analysis of biofilm formation on implant materials. - Henryke Rath; Sascha Nico Stumpp; Meike Stiesch (PLoS ONE)
Since the introduction of modern dental implants in the 1980s, the number of inserted implants has steadily increased. Implant systems have become more sophisticated and have enormously enhanced patients' quality of life. Although there has been tremendous development in implant materials and clinical methods, bacterial infections are still one of the major causes of implant failure. These infections involve the formation of sessile microbial communities, called biofilms. Biofilms possess unique physical and biochemical properties and are hard to treat conventionally. There is a great demand for innovative methods to functionalize surfaces antibacterially, which could be used as the basis of new implant technologies. Present, there are few test systems to evaluate bacterial growth on these surfaces under physiological flow conditions. We developed a flow chamber model optimized for the assessment of dental implant materials. As a result it could be shown that biofilms of the five important oral bacteria Streptococcus gordonii, Streptococcus oralis, Streptococcus salivarius, Porphyromonas gingivalis, and Aggregatibacter actinomycetemcomitans, can be reproducibly formed on the surface of titanium, a frequent implant material. This system can be run automatically in combination with an appropriate microscopic device and is a promising approach for testing the antibacterial effect of innovative dental materials.